Is Ethical Governance Enough? Green Finance, Disclosure, and the Islamic Corporate Ethos - Abbas, Djamila (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study investigates how Islamic business ethics, risk disclosure, and Islamic corporate social responsibility (i-CSR) jointly influence firm value within Shariah-compliant firms listed on the Jakarta Islamic Index from 2020 to 2024. By integrating ethical imperatives with market-based signaling theory, the research offers a novel lens through which capital market behavior and corporate governance are interpreted in Islamic financial contexts. Employing panel data regression, the analysis reveals that enhanced ethical disclosure, particularly when aligned with Islamic principles, positively correlates with firm valuation, contingent upon governance dynamics and stakeholder perceptions. Findings support the argument that Islamic ethical commitments are not merely symbolic but materially relevant in investor assessment and capital structure decisions. This paper contributes to expanding the theoretical discourse on Islamic finance by fusing doctrinal ethics with empirical asset valuation. The results suggest that firms adopting transparent, faith-conscious governance may command stronger market trust and long-term strategic advantage.